KESEJAHTERAAN PSIKOLOGIS DITINJAU DARI REGULASI EMOSI PADA IBU YANG MENDAMPINGI ANAK SEKOLAH DARI RUMAH - Maya Arizqina Fauziah; Ruseno Arjanggi (UIN Sunan Kalijaga, 2021)
The increasing burden of mothers during the pandemic by accompanying children's learning during school from home in the pandemic is an additional burden that teachers have previously done in schools. The increasing responsibility of the mother stimulated a decrease in the feeling of well-being in mother. The purpose of this study was to test the hypothesis that there is a positive relationship between emotional regulation and the psychological well-being of mothers who accompany their children to study from home during Covid 19 pandemic. Participants of this study were mothers who had children at the formal education stage in elementary school. A total of 110 mothers became participants in the scale try out of research instruments and 152 mothers joined as participants in the study. Two measuring instruments used in this research were emotional regulation scale and emotional well-being scale. Test result of emotional regulation scale obtained internal consistency α=0,77 and emotional well-being scale obtained internal consistency α=0,85. Hypothetical test by biserial correlation Pearson result found that emotional regulation correlated with emotional well-being. This study implies that better regulation of emotions that mothers have will contribute to improve psychological well-being.Bertambahnya beban ibu selama pandemi Covid-19 dengan mendampingi belajar anak selama bersekolah dari rumah merupakan beban tambahan yang sebelumnya banyak dilakukan oleh guru di sekolah. Bertambahkan tanggung jawab ini memungkinkan terjadinya penurunan perasaan sejahtera pada ibu. Tujuan penelitian ini adalah untuk menguji hipotesis penelitian yaitu ada hubungan positif antara regulasi emosi dengan kesejahteraan psikologis pada Ibu yang mendampingi anak sekolah dari rumah selama masa pandemic Covid-19. Partisipan penelitian ini yaitu 110 ibu sebagai partisipan uji coba alat ukur dan 152 ibu sebagai partisipan penelitian. Dua alat ukur digunakan dalam penelitian ini yaitu skala regulasi emosi dan skala kesejahteraan emosi. Hasil uji coba skala regulasi emosi diperoleh internal konsistensi α=0,77 dan skala kesejahteraan emosi diperoleh internal konsistensi α=0,85. Hasil uji hipotesis dengan menggunakan korelasi dari pearson menemukan bahwa regualsi emosi berkorelasi dengan kesejahteraan emosi. Penelitian ini memiliki implikasi bahwa semakin baik regulasi emosi yang dimiliki ibu akan memiliki kontribusi terhadap terbentuknya kesejahteraan psikologis yang semakin baik pula.